The place reconstruction, government practice, and ethnic identity of Chinese folk song Zhangjiachuan Hua'er - Zhao, Lin; Ang, Mei Foong (Human Resources Management Academic Research Society (HRMARS), 2024)
The research focuses on elucidate the musical and cultural connotations embodied in the place reconstruction, governmental practice, and ethnic identity associated with the Chinese local folk song Zhangjiachuan Hua'er, through the integration of diachronic and synchronic studies. This study is based on Tuan's (1977) theory of "place and space" and used the ethnographic fieldwork method of ethnomusicology to conducted research. The findings indicated: 1) The "local knowledge" embedded in Zhangjiachuan Hua'er exhibits diachronic development. Characterized by ethnic integration, folklore, lyrical content, and symbolic elements, Zhangjiachuan Hua'er exemplifies local features that evoke a "sense of place", grounded in experiences, self, and ethnic traits. 2) Owing to the role transformation of Zhangjiachuan Hua'er, the local distinct identity of Zhangjiachuan Hua'er has been brought outstanding via the creation of cultural symbols as well as Innovative practices of local government, which achieved acceptance and recognition from local government, ethnic group, and so forth and so on. Thus, the traditional symbol meaning of Zhangjiachuan Hua'er has been extended through synchronic exploration. 3) The crux of ethnic groups' shifting identification with Zhangjiachuan Hua'er lies in the interaction and integration of "self" and "the other" within the local context. This research extends the theoretical understanding of the dynamic evolution of "human-land" relationships through the interplay of diachronic and synchronic mechanisms in local reconstruction. This study not only advances theoretical understanding of how music culture influences the dynamics of "human-land" relationships, but also fosters interdisciplinary dialogue and enhances comprehension of folk music's role in modern societies, particularly at the nexus of globalization and localization. The integration of this theoretical framework with empirical research provides a valuable reference for investigating musical and cultural phenomena in other regions.